Self-* and P2P for Network Management Design Principles and Case Studies - Marquezan, Clarissa Cassales; Granville, Lisandro Zambenedetti; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
The network management community has been pushed towards the design of alternative management approaches able to support heterogeneity, scalability, reliability, and minor human intervention. The employment of self-* properties and Peer-To-Peer (P2P) are seen as promising alternatives, able to provide the sophisticated solutions required. Despite being developed in parallel, and with minor direct connections perceived between them, self-* properties and P2P can be used concurrently. In Self-* and P2P for Network Management: Design Principles and Case Studies, the authors explore the issues behind the joint use of self-* properties and P2P, and present: a survey relating autonomic computing and self-* properties, P2P, and network and service management; the design of solutions that explore parallel and cooperative behavior of management peers; the change in angle of network management solution development from APIs, protocols, architectures, and frameworks to the design of management algorithms.
Foreword -- Preface -- Introduction -- State of the Art -- Principles of the Self-* P2P Design -- Case Study I: Reliability of Monitoring Platforms -- Case Study II: Resource Management of Network Virtualization -- Results Discussion -- Conclusions.
Keywords: Computer science; Computer Communication Networks; Computer Science; Computer Communication Networks